Pengaruh Penjaruman Titik Akupunktur Feishu (BL 13) dan Zusanli (ST 36) Terhadap Jumlah Limfosit CD4+ Pada Model Tikus Putih Asma - Balgis (Jurnal Kedokteran Indonesia, 2011)
Background: Asthma prevalence is increasing in developing and developed countries. CD4+ Th2 Celland its product play an important role in asthma pathogenesis. This study examined the effect ofneedling at Feishu (BL13) and of Zusanli (ST36) acupoints in decreasing CD4+ lymphocyte counts inasthmatic rat model.Methods: This was a randomized-controlled laboratory trial with a sample of 27 white Spargue Dawleyrats. The sample was divided into three groups by randomization: a control group (K) not given atreatment, treatment group 1 (PI) exposed with ovalbumin (OVA), and treatment group II (PII)exposed with OVA and acupuncture. OVA were given by intraperitoneal on days 1 to 14, followed withinhaled OVA on days 21, 23, 25, 27, and 29. Acupuncture was provided at Feishu (BL13) and Zusanli(ST36) points for 10 days, starting on day 21 to 30. Continuous wave electro-stimulation at 2 Hz frequencywas given for 15 minutes, with its intensity varied to induce muscle contractions around needling area.The white rats were killed on day 31 by neck dislocation. The lungs were stained with immunehistochemistry for histologic examination. The data were analyzed using One-way Anova and Post HocTest.Results: One-way Anova showed statistically significant difference in CD4+ lymphocyte counts amonggroups (p<0.001).Conclusion: Needling at Feishu (BL13) and Zusanli (ST36) acupoints decreases CD4+ lymphocyte countssignificantly at treatment group II. But this decrease does not reach CD4+ lymphocyte counts as it is inthe control group.Keywords: acupuncture, CD4+ lymphocyte, asthma.